Factors That Influence Community Behavior Of Incidental Defeat at Desa Jawa Belakang, Kecamatan Langsa, Kota Langsa - Nurmaliah; Asriwati; Neni Ekowati Januariana (International Archives of Medical Sciences and Public Health, 2022)
Disposal of feces (feces and urine) that is not according to the rules. Open defecation can be influenced by several factors, including factors of knowledge, education, habits (habit) and others. The purpose of this study was to determine the factors influencing the behavior of people to defecate openly in the village of Jawa Behind Langsa Kota. This type of research is an analytical survey method with a cross sectional approach. The research was carried out in the area of ??Java Behind Village, Langsa Kota District. The population of this study is the population of the village of Jawa Behind totaling 605 families. The sample in this study was 86 families. Sampling was done by simple random. Data analysis used univariate, bivariate and multivariate analysis. The results showed that there were 56 people with positive defecation (65.1%) and 30 people with negative defecation (34.9%). The results of the chi-square statistical test showed that the variables of knowledge, attitude, education, income, latrine ownership and the role of health workers had an influence on open defecation behavior with p <0.05. Simultaneously, the results showed that education and latrine ownership were the most dominant factors influencing people's open defecation behavior. It is hoped that the community will always explore and seek information about public health and have a high response and responsiveness in carrying out the Stop Open Defecation program either individually or in groups by always being environmental sanitation and not practicing open defecation.